2010
DOI: 10.3846/jcem.2010.01
|View full text |Cite
|
Sign up to set email alerts
|

The Driving Factors of China's Public-Private Partnership Projects in Metropolitian Transportation Systems: Public Sector's Viewpoint

Abstract: Abstract. In recent years, China needs far more financing for transportation infrastructure than can be provided by the government alone. Meanwhile the capacity of the Chinese government to provide public services on its own in an effective and efficient way is being questioned and reassessed at various levels. Accordingly, the involvement of private investors in the development of Metropolitan Transportation Systems (MTS) has been promoted by the Chinese public sector by means of adopting the Public Private P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 26 publications
2
37
0
Order By: Relevance
“…Zhang suggested that if toll levels exceed the users' affordability for a service, public satisfaction will become poor, and the PPP project may be ruined by strong public opposition [13]. The results of Li et al, Ng et al and Aziz also provided some similar evidence for the importance of an appropriate service price in achieving the sustainability of a PPP and maintaining social stability [12,40,49]. Therefore, a reasonable service price is very important to enhance the project revenue, improve public satisfaction and maintain a sustainable partnership.…”
Section: Interrelationships Among the Csfssupporting
confidence: 59%
See 3 more Smart Citations
“…Zhang suggested that if toll levels exceed the users' affordability for a service, public satisfaction will become poor, and the PPP project may be ruined by strong public opposition [13]. The results of Li et al, Ng et al and Aziz also provided some similar evidence for the importance of an appropriate service price in achieving the sustainability of a PPP and maintaining social stability [12,40,49]. Therefore, a reasonable service price is very important to enhance the project revenue, improve public satisfaction and maintain a sustainable partnership.…”
Section: Interrelationships Among the Csfssupporting
confidence: 59%
“…Additionally, these existing factors are good references for studying the sustainable implementation of the PPP project. Among them, all of the CSFs mainly involved four types, i.e., the public sector-related factor [11,17,29], the private sector-related factor [12,13], the environment-related factor [26,29,30] and the factor of the process of services provision [11,16,45,47,49]; these findings are also good references for determining the CSFs and questionnaire design. However, all of the previous studies determined the critical success factor for the PPP project, but the interrelationships among CSFs were ignored; and the variable of the public in PPP is also not included in the CSF framework constructed in the previous research.…”
Section: Critical Success Factors Of Ppp In Infrastructure Projectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Public-Private Partnership (PPP) is applied for making the long-term alliances between government and private developers for private resource and the public services (Ashuri et al 2010). PPP is considered an important means of solving the problems of insufficient funds for constructing public projects and inefficient public projects (Yuan et al 2010;Cheung et al 2010). If participating developers or private investors involved in managing public enterprises are self-disciplined and effectively organized, the abuse and degradation of common resources can be successfully prevented (Ostrom 1990).…”
Section: Introductionmentioning
confidence: 99%